2000
DOI: 10.1161/01.res.86.8.897
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-Dependent Vasodilators Cross-Activate the cGMP-Dependent Protein Kinase to Stimulate BK Ca Channel Activity in Coronary Artery Smooth Muscle Cells

Abstract: Abstract-cAMP-dependent vasodilators are used to treat a variety of cardiovascular disorders; however, the signal transduction pathways and effector mechanisms stimulated by these agents are not fully understood. In the present study we demonstrate that cAMP-stimulating agents enhance the activity of the large-conductance, calcium-activated potassium (BK Ca ) channel in single myocytes from coronary arteries by "cross-activation" of the cGMP-dependent protein kinase (protein kinase G, PKG). Single-channel patc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
142
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(155 citation statements)
references
References 54 publications
(63 reference statements)
12
142
1
Order By: Relevance
“…that regulation occurs through a membrane-delimited pathway. This conclusion is consistent with other electrophysiological studies of the BK channel, where channel regulation by kinases has also been demonstrated in excised patches (7,8,29,(37)(38)(39)(40)(41)(42)(43). Our biochemical assays (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…that regulation occurs through a membrane-delimited pathway. This conclusion is consistent with other electrophysiological studies of the BK channel, where channel regulation by kinases has also been demonstrated in excised patches (7,8,29,(37)(38)(39)(40)(41)(42)(43). Our biochemical assays (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we observed colocalization of caveolin-1 and PKG in rat aorta endothelium. Cross-talk between cGMP and cAMP has been reported (Dhanakoti et al, 2000;White et al, 2000). cGMP can also activate PKA (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth noting that while the partial agonism of cAMP contributes to cyclic nucleotide selectivity for cGMPcontrolled signaling pathways, previous studies have suggested that selected signaling responses are influenced by cAMP via modulation of PKG activity, rather than cAMP-dependent proteins such as PKA (5,51). A possible explanation for this phenomenon is that as the intracellular cAMP concentration rises, the minimal cGMP concentration necessary for full PKG activation increases, and the shape of the cGMP-dependent activation profile of PKG may also change.…”
Section: Discussionmentioning
confidence: 99%